IMPLEMENTATION OF PjBL-ETHNOSCIENCE-BASED CHROMATOGRAPHY TEXTBOOK WITH AUGMENTED REALITY SUPPORT TO IMPROVE CRITICAL THINKING SKILLS - Sri Adelila Sari; Hanisah Hasibuan; Corrienna Abdul Talib (JCER (Journal of Chemistry Education Research), 2026)
The purpose of this study was to examine how using a chromatography textbook based on Project-Based Learning (PjBL) combined with ethnoscience and augmented reality (AR) improved students' critical thinking abilities. This study employed a single-group pretest-posttest pre-experimental design and a quantitative methodology. Out of the 192 students in the population, 32 chemical education students were chosen for the sample using purposive sampling. A ten-item essay test that was modified from Ennis' indications was used to measure critical thinking abilities. N-Gain analysis and the Shapiro-Wilk normality test were used to examine the data. The data were found to be regularly distributed (Sig. = 0.458 > 0.05). With an N-Gain of 0.70, which is considered high, the average pre-test score rose from 56.96 to 87.03 on the post-test. These results show that students' critical thinking abilities were successfully enhanced by the created textbook.